Thrombotic microangiopathy in untreated myeloma patients receiving carfilzomib, cyclophosphamide and dexamethasone on the CARDAMON study. (1st March 2021) - Camilleri, Marquita; Cuadrado, Maria; Phillips, Elizabeth; Wilson, William; Jenner, Richard; Pang, Gavin; Kamora, Sumaiya; Streetly, Matthew; Popat, Rakesh; Bygrave, Ceri; Owen, Roger; Cavenagh, James; et al.
Summary: Proteasome inhibitors have been associated with thrombotic microangiopathy (TMA) — a group of disorders characterised by occlusive microvascular thrombosis causing microangiopathic haemolytic anaemia, thrombocytopenia and end‐organ damage. To date, carfilzomib‐associated TMA has predominantly been described in relapsed/refractory myeloma patients. We report eight patients with newly diagnosed myeloma who experienced TMA events while receiving carfilzomib on the phase II CARDAMON trial. The first three occurred during maintenance single‐agent carfilzomib, two occurred at induction with carfilzomib given with cyclophosphamide and dexamethasone (KCd) and three occurred during KCd consolidation. At TMA presentation 6/8 were hypertensive; 7/8 had acute kidney injury and in three, renal impairment persisted after resolution of TMA in other respects. The mechanism of carfilzomib‐associated TMA remains unclear, though patients with known hypertension seem particularly susceptible. Given the first three cases occurred during maintenance after a longer than five‐week treatment break, a protocol amendment was instituted with: aggressive hypertension management, carfilzomib step‐up dosing (20 mg/m 2 on day 1) at start of maintenance before dose escalation to 56 mg/m 2 maximum, and adding 10 mg dexamethasone as premedication to maintenance carfilzomib infusions. No further TMA events occurred during maintenance following this amendment and the TMA incidence reduced from 4·2 to 1·6 per 1 000 patient cycles.